2021
DOI: 10.3390/ijerph18179259
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Preventive Practices and Risk Communication towards COVID-19: A Cross-Sectional Study in Bangladesh

Abstract: Bangladesh recently experienced a COVID-19 second wave, resulting in the highest number of new cases and deaths in a single day. This study aims to identify the challenges for COVID-19 preventive practices and risk communications and associated factors among Bangladeshi adults. A cross-sectional survey was conducted between December 2020 and January 2021 involving 1382 Bangladeshi adults (aged ≥ 18-years) in randomly selected urban and rural areas from all eight divisions in Bangladesh. Descriptive data analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Lüdecke and von dem Knesebeck [ 21 ] found that in a German sample, individuals with lower educational attainment were less likely to engage in social distancing or engage in appropriate hand washing behavior—although the observed effect sizes were small to negligible. Those findings were consistent with other work [ 23 ], which found that lower educational attainment and employment in agricultural and domestic labor (compared to business sector) predicted lower levels of social distancing and hand washing among Iranian adults.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…Lüdecke and von dem Knesebeck [ 21 ] found that in a German sample, individuals with lower educational attainment were less likely to engage in social distancing or engage in appropriate hand washing behavior—although the observed effect sizes were small to negligible. Those findings were consistent with other work [ 23 ], which found that lower educational attainment and employment in agricultural and domestic labor (compared to business sector) predicted lower levels of social distancing and hand washing among Iranian adults.…”
Section: Introductionsupporting
confidence: 93%
“…Suen and colleagues [ 10 ], for example, found that women were more likely to perform proper hand hygiene techniques compared to men. Their findings were echoed in research among Bangladeshi men who have been found to have significantly greater odds of experiencing challenges with practicing COVID-related preventive behaviors [ 23 ]. However, in Saudi Arabian samples, men were more likely to wash their hands with soap and water than women [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high antibody positivity in this population suggests that adherence and adequacy of the practices might be limited. A recent cross-sectional study from Bangladesh reported that nearly 71% of respondents indicated difficulties adhering to the recommended COVID-19 preventive practices [ 24 ]. Lack of interest in using masks, crowded living conditions, inadequate information on the proper application of protective measures, inadequate handwashing and sanitation facilities, and negative influences on family/friends were the main barriers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Germany suggests that educational background was positively associated with protective behaviors among the general public (24) while a study from Switzerland suggests the opposite association among young people (25). In Bangladesh, information on the proper use of protective measures from the government were identified as the drivers of COVID-19 protective behaviors (26). Findings from Nigeria and the USA showed that individuals who perceived greater risks of COVID-19 infection were more likely to adopt protective behaviors (27,28).…”
Section: Introductionmentioning
confidence: 99%